Robust Control Of Sampled Data Systems - AL-Sunni, Fouad (2020)
The authors present robust stability bounds for sampled data systems. The bounds are derived for the general case of additive perturbation in a system, and the control gain matrices for continuous time systems under discrete state feedback control. They then present a numerical controller design algorithm based on the derived bounds.Examples are used for demonstration.